Stabilization and H∞ Control of Nonlinear Switched Hamiltonian Systems Subject to Actuator Saturation - Li, Han; Wei, Airong (Asian journal of control, 2017)
This paper investigates the stabilization and H∞ control problem of nonlinear switched Hamiltonian systems (NSHSs) subject to actuator saturation (AS) under arbitrary switching paths. First, based on the saturating actuator property, an appropriate state feedback is designed under a realistic assumption for the stabilization of NSHSs with AS. Then, an H∞ controller is designed for NSHSs subject to AS with external disturbances in order to attenuate the disturbances. Futhermore, the results obtained for NSHSs are applied to study the stabilization and H∞ control of switched nonlinear systems with AS via the Hamiltonian realization method. Finally, simulation examples show the efficiency of the methods and results proposed in this paper.